Vanadate‐Based Fibrous Electrode Materials for High Performance Aqueous Zinc Ion Batteries - Qimeng Wang; Jianping Wu; Mingming Wang; Haizhou Yu; Xiaoyan Qiu; Wei Chen (Advanced Science, 2024)
Abstract Aqueous zinc‐ion batteries (AZIBs) are considered as attractive energy storage systems with great promise owing to their low cost, environmental friendliness and high safety. Nevertheless, cathode materials with stable structure and rapid diffusion of zinc ions are in great demand for AZIBs. In this work, a new kind of potassium vanadate compound (KV3O8) is synthesized with fibrous morphology as an excellent cathode material for AZIBs, which shows outstanding electrochemical performance. KV3O8 exhibits a high discharge capacity of 556.4 mAh g−1 at 0.8 A g−1, and the capacity retention is 81.3% at 6 A g−1 even after a long cycle life of 5000 cycles. The excellent performance of the KV3O8 cathode is benefited from the structural stability, sufficient active sites, and high conductivity, which is revealed by in situ X‐ray diffraction and various other characterizations. This work offers a new design strategy into fabricating high efficiency cathode materials for AZIBs and beyond.